EDUCATION ON FEEDING INFANTS AND CHILDREN ON KNOWLEDGE AND BEHAVIOR OF MOTHERS IN FEEDING WASTING CHILDREN - Retno Palupi Yonni Siwi; Heppy Indrawati; Miftakhur Rohmah; Candra Wahyuni; Intan Fazrin; Riza Tsalatsatul Mufida (Universitas Karya Husada Semarang, 2024)
The high incidence of wasting is caused by lack of nutrition in children, thus affecting the growth and development of childr en. Thepurpose to analyze feeding education in infants and children on the knowledge and behavior of mothers in feeding wasting ch ildren.The design of this study was pre-experimental with a one group pretest posttest design approach, the sample was mothers of wastingtoddlers as many as 30 respondents, using purposive sampling techniques. The independent variable was infant and child feedingeducation and the dependent variable was knowledge and behavior, using extension event unit instruments, leaflets andquestionnaires, data analysis using Paired T-test. The increase in knowledge was marked by a difference in the total mean value of23.87 and maternal behavior and a total difference in the mean value of 21.7 after education. The results of statistical tests obtainedρ-values of 0.000< 0.05 and a fairly strong correlation of 0.568 knowledge variables and 0.413 on behavioral variables means thatthere is a strong enough influence between education on knowledge and behavior. Counseling activities can help mothers gainunderstanding and practical skills in infant and child feeding practices so as to prevent wasting.